PENGARUH INTERNET TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KELAS XI IPS SEKOLAH MENENGAH ATAS NEGERI 1 TAMBANG KABUPATEN KAMPAR TAHUN AJARAN 2020/2021 - Habli, Arminal; Ibrahim, Bedriati; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Learning resources are all resources that can be used for the benefit of the teaching process or activity, either directly or indirectly, outside the students (environment) who complete themselves during the teaching process. The purpose of this study were (1) to determine the use of the internet in history subjects in class XI IPS SMA Negeri 1 Tambang, Kampar Regency. (2) To find out the student learning outcomes in history subjects in class XI IPS at SMA Negeri 1 Tambang, Kampar Regency. (3) To determine the effect of the internet on student learning outcomes in history subjects in class XI IPS at SMA Negeri 1 Tambang, Kampar Regency, academic year 2020/2021. The method in this research is to use quantitative methods. The population in this study were 117 students of class XI IPS at SMA Negeri 1 Tambang Kampar Regency, which consisted of 4 classes, the sample in this study were class XI1 IPS and XI2 IPS, totaling 58 students. The data that has been collected is then analyzed using a percentage as a preliminary analysis and the follow-up analysis uses linear regression analysis, while the learning outcomes of students who reach completion are 37 students and those who do not complete are 21 students. The hypothesis in this study is that internet learning resources have an effect on the variable learning outcomes of students in class XI IPS at SMA Negeri 1 Tambang, with the amount of influence given is 49.1%.Key Words: Internet and Learning Outcomes.